The monotheizing process: its origins and development - Sanders, James A. (Cascade Books, 2014)
Judaism, Christianity, and Islam claim to be monotheistic, but none of them actually is; none of the three has yet arrived at the true monotheism the Bible and the Qur'an mandate: that is, belief in there being but One God of All. Each often claims its concept of God is the One God despite the fact that the Bible and the Qur'an insist that the true God is indefinable and incomprehensible. Many passages of the Bible are polytheistic, and yet the Judaism that emerged out of the exile claimed to believe in One God. Critically moving from the older passages through to the later, careful readers ar